Selective Gene Transfer to the Retina Using Intravitreal Ultrasound Irradiation - Shozo Sonoda; Katsuro Tachibana; Toshifumi Yamashita; Makoto Shirasawa; Hiroto Terasaki; Eisuke Uchino; Ryo Suzuki; Kazuo Maruyama; Taiji Sakamoto (Journal of Ophthalmology)
This paper aims to evaluate the efficacy of intravitreal ultrasound (US) irradiation for green fluorescent protein (GFP) plasmid transfer into the rabbit retina using a miniature US transducer. Intravitreal US irradiation was performed by a slight modification of the transconjunctival sutureless vitrectomy system utilizing a small probe. After vitrectomy, the US probe was inserted through a scleral incision. A mixture of GFP plasmid (50 μL) and bubble liposomes (BLs; 50 μL) was injected into the vitreous cavity, and US was generated to the retina using a SonoPore 4000. The control group was not exposed to US. After 72 h, the gene-transfer efficiency was quantified by counting the number of GFP-positive cells. The retinas that received plasmid, BL, and US showed a significant increase in the number (average ± SEM) of GFP-positive cells (32±4.9; n=7; P<0.01 ). No GFP-positive cells were observed in the control eyes (n=7). Intravitreal retinal US irradiation can transfer the GFP plasmid into the retina without causing any apparent damage. This procedure could be used to transfer genes and drugs directly to the retina and therefore has potential therapeutic value.